Erectile dysfunction and pcsychoemotional state in ischemic heart disease patients undergone coronary artery bypass grafting - Ye. V. Pomeshkin; A. I. Neimark; S. A. Pomeshkina; O. L. Barbarash (Бюллетень сибирской медицины)
The impact of erectile dysfunction on psychoemotional state of patients undergone coronary artery bypass graft surgery was evaluated. The International Index of Erectile Function, postcompression cavernous artery dilation test, nocturnal penile tumescence recording and psychophysiological exam were used. It was found that ischemic heart disease patients have higher incidence of associated psychoemotional and erectile dysfunctions.